Typological Aspects of Adequate Translation Methods of “Spirituality” Nominative Units into English - Mehrinigor Bahodirovna, Akhmedova (International Journal of Psychosocial Rehabilitation, 2020)
One of the key factors in the global presence of the Uzbek language is that, firstly, it becomes one of the Internet languages, and secondly, the translations of examples of Uzbek national spirituality, including the translation of literary works into the world languages. Delivery of works of art, expressions of the Uzbek national spirituality, to students around the world plays an important role in the process of integration with the world culture and science. There are a number of problems in translating works of national mentality and spirituality, especially in English. In particular, a number of questions and problems arise when translating only the concepts of one ethnicity into other languages, that is, elements of the concept of one nation in another language, in which a systematic conceptual dictionary can assist the interpreter.